Improved Photocatalytic Water Splitting Activity of Highly Porous WO3 Photoanodes by Electrochemical H+ Intercalation - Levinas, Ramunas; Tsyntsaru, Natalia; Murauskas, Tomas; Cesiulis, Henrikas (Frontiers in Chemical Engineering, 2021)
WO3 photoanodes are widely used in photoelectrochemical catalysis, but as regular the as-synthesized material is annealed before application. It is therefore desirable to explore less energy-intensive treatments. In this study, WO3 films of up to 3.9 µm thickness were obtained by galvanostatic anodization in a neutral-pH Na2SO4 and NaF electrolyte, also containing a NaH2PO2 additive (to suppress O2 accumulation on the pore walls). Additionally, the WO3 photoanodes were modified by applying a cathodic reduction (H+ intercalation) and anodic activation treatment in-situ. XPS spectra revealed that intercalation modifies WO3 films; the amount of W5+-O and O-vacancy bonds was increased. Furthermore, subsequent activation leads to a decrease of the W5+ signal, but the amount of O-vacancy bonds remains elevated. The as-prepared and reduced (intercalated & activated) films were tested as OER photoanodes in acidic 0.1 M Na2SO4 media, under illumination with a 365 nm wavelength LED. It was observed that thinner films generated larger photocurrents. The peculiarities detected by XPS for reduced films correlate well with their improved photocatalytic activity. Photo-electrochemical impedance and intensity modulated photocurrent spectroscopies were combined with steady-state measurements in order to elucidate the effects of H+ intercalation on photoelectrochemical performance. The reduction results in films with enhanced photoexcited charge carrier generation/separation, improved conductivity, and possibly even suppressed bulk recombination. Thus, the intercalation & activation adopted in this study can be reliably used to improve the overall activity of as-synthesized WO3 photoanodes, and particularly of those that are initially poorly photoactive.